Diseño y construcción de un Banco Didáctico de engranajes para transmisión de potencia en la Universidad Antonio Nariño sede Neiva. (2021)
The students of the Mechanical Engineering program at the Universidad Antonio Nariño, Neiva, do not have a bench that allows them to perform laboratories for combined gear systems practices (pulley-belt-pinions) since those currently available only allow the calculation of spur and helical gears, which does not allow complementing the curriculum of the subject of mechanical design I and II. According to the above, the research work proposed aims to design and build a didactic bench of gears for power transmission at the Universidad Antonio Nariño, Neiva. The methodology designed to achieve this objective includes 4 phases, which begin with the identification of the different types of power transmissions and selection of those that will be part of the didactic bench; the prototype of the didactic bench, as well as calculations and selection of materials for its construction and the fifth phase that implies the elaboration of laboratory guides and operation manual of the bench for the students of the mechanical engineering program of the Universidad Antonio Nariño, Neiva; As a result, a didactic power transmission gear bench was built with a 1 HP motor, which works at an angular speed of 1800 rpm, with three transmission trains; the developed bench allows students to strengthen their skills in the calculation of power transmission systems such as torques, speed, power train ratio.